Adding flexibility to stiff masonry shear walls: an exploratory study. Issue 4 (2nd October 2017) - Abrams, Daniel P.
Abstract: A novel structural engineering design approach is described where flexibility can be added to a masonry shear wall system with the use of a series of steel connector plates that transfer seismic story shear forces to individual masonry wall panels. This innovative form of building construction is termed "hybrid masonry" since structural steel frames resist lateral forces with the help of engineered structural masonry panels. The steel connector plates are undersized to have considerable flexibility and a relatively low flexural strength. Acting as fuses, these connectors will not only reduce the overall lateral stiffness of a building system, but also dissipate seismic energy through hysteresis. In so doing, the integrity of the structural system to withstand earthquake motions is enhanced. As well, repair costs will be minimized since masonry damage can be circumvented. Thus, maintenance issues associated with costly seismic repairs can be avoided. Results of computations are given that show how lateral story stiffness and seismic demand forces can be reduced. A simple two-story, one-bay steel frame with reinforced masonry panels is used as an example to demonstrate load sharing when connector strength and stiffness are varied. In general, new innovations in structural design are proposed where structural steel and structural masonry are paired to result in a new standard of structural integrity that exceeds the sum of the parts.